Prompt rewetting of drained peatlands reduces climate warming despite methane emissions - Anke Günther (Nature Portfolio, 2020)
Drained peatlands are sources of CO2, and though rewetting could curb emissions, this strategy results in elevated methane release. Here, the authors model peatland emissions scenarios and show that rewetting is a critical way to mitigate climate change despite potential methane increases.